Effectiveness of hemostatic powders in lower gastrointestinal bleeding: a systematic review and meta-analysis - Facciorusso, Antonio; Bertini, Marco; Bertoni, Michele; Tartaglia, Nicola; Pacilli, Mario; Ramai, Daryl; Mohan, Babu P.; Chandan, Saurabh; Ambrosi, Antonio; Sacco, Rodolfo (Endoscopy International Open, 2021)
Background and study aims There is limited evidence on the effectiveness of hemostatic powders in the management of lower gastrointestinal bleeding (LGIB). We aimed to provide a pooled estimate of their effectiveness and safety based on the current literature.Patients and methods Literature review was based on computerized bibliographic search of the main databases through to December 2020. Immediate hemostasis, rebleeding rate, adverse events, and mortality were the outcomes of the analysis. Pooled effects were calculated using a random-effects model.Results A total of 9 studies with 194 patients were included in the meta-analysis. Immediate hemostasis was achieved in 95 % of patients (95 % confidence interval [CI] 91.6 %–98.5 %), with no difference based on treatment strategy or bleeding etiology. Pooled 7- and 30-day rebleeding rates were 10.9 % (95 %CI 4.2 %–17.6 %) and 14.3 % (95 %CI 7.3 %–21.2 %), respectively. Need for embolization and surgery were 1.7 % (95 %CI 0 %–3.5 %) and 2.4 % (95 %CI 0.3 %–4.6 %), respectively. Overall, two patients (1.9 %, 95 %CI 0 %–3.8 %) experienced mild abdominal pain after powder application, and three bleeding-related deaths (2.3 %, 95 %CI 0.2 %–4.3 %) were registered in the included studies.Conclusion Novel hemostatic powders represent a user-friendly and effective tool in the management of lower gastrointestinal bleeding.